Synthesis method and separation application of graded-pore single crystal HP-MIL-101
By introducing mesoporous pores into MOF materials, the fractionated pore single crystal HP-MIL-101 was prepared, which solved the problem of micropores limiting macromolecules in existing MOF materials, achieved adjustable mesoporous size, and improved adsorption and separation of materials performance.
Patent Information
- Application Number
- CN202411613640.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing MOF materials are mainly microporous, which hinder the diffusion of macromolecules and the interaction with active sites in the MOF structure, and limit their applications in macromolecules adsorption and separation, drug delivery, etc.
By uniformly mixing the metal salt and organic ligand in water and carrying out reflux reaction, a fractionated pore single crystal HP-MIL-101 was prepared to maintain the original micropores and structural stability, and at the same time, the mesoporous size was introduced, and the mesoporous size was adjustable.
The introduction of mesoporous pore structure is achieved on the basis of maintaining the stability of the micropore structure, which enhances the specific surface area and mesoporous adjustability of the material, and improves its performance in adsorption and separation.
Smart Images

Figure HDA0005131566240000011 
Figure HDA0005131566240000021 
Figure HDA0005131566240000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of MOF materials, and in particular relates to a synthesis method of graded-pore single crystal HP-MIL-101 and separation application thereof. Background Art
[0002] Metal-organic framework (MOFs) materials, also known as porous coordination polymers (PCPs), are an emerging and very abundant class of microporous materials. MOFs materials are a group of crystalline materials with a three-dimensional pore structure composed of metal atoms and organic ligands. The spatial pairing of metal atom centers and various organic ligands gives the material a controllable pore size and adds many unique physical and chemical properties. It also has the advantages of ultra-high porosity and specific surface area. Among them, the MILs material reported by Ferry et al. is the most representative, and MILs material is also one of the most studied materials in MOF. Most of the MIL series materials use Cr 3+ , Fe 3+ 、Al 3+ As metal ion clusters, terephthalate derivatives and terephthalate analogs are used as organic ligands and ligands. Among them, MIL-101 not only has ultra-high porosity specific surface area and strong stability, but also has two internal dimensions of approximately and The corresponding pore volumes are and The cage has a size of The large cage has both a pentagonal window and a These features make it play a vital role in functional applications such as catalysis and adsorption separation. However, the two most representative mesoporous cages are connected to the outside world through microporous channels, which impose certain restrictions on the transport of substrate molecules and have an adverse effect on their applications.
[0003] However, most MOF materials reported to date are microporous (pore size less than 2 nm), and the small pore size inherently hinders the diffusion of macromolecules and limits their interaction with active sites in the MOF structure. Hierarchical MOF materials have attracted great interest due to their potential applications in macromolecular adsorption and separation, bulk drug delivery, and heterogeneous catalysis, in which mesopores or macropores have specific properties in terms of fast molecular diffusion and mass transfer. In addition, microporous MOFs will also benefit from additional mesopores to increase accessibility to the microporous cavities containing metal centers. Most notably, the preparation of mesopores in microporous MOFs combines the advantages of nanoporous materials with those of the parent microporous MOF materials, which can combine the valuable characteristics of microporous and mesoporous or even macroporous components, while the size of the mesopores is adjustable, which is beneficial for applications in different scenarios. However, how to prepare hierarchical pore MOF materials by simple methods and achieve adjustable and controllable mesopore size is a top priority. Summary of the invention
[0004] The purpose of the present invention is to provide a synthesis method of graded pore single crystal HP-MIL-101 and its separation application, which has mesopore size and controllable mesopore size while maintaining the original micropore and structural stability.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for synthesizing a graded-pore single crystal HP-MIL-101 is provided, comprising the following steps:
[0007] The metal salt and the organic ligand are uniformly mixed in water to obtain a precursor solution, which is then heated for reflux reaction. After the reaction is completed, the graded hole single crystal HP-MIL-101 is obtained; wherein:
[0008] The molar volume ratio of organic ligand to water is 1 mol:30-100 L;
[0009] The reflux reaction time is: 40-96h.
[0010] According to the above scheme, the metal salt and the organic ligand are mixed in water and then ultrasonicated for 20-40 minutes to mix them evenly.
[0011] According to the above scheme, the heating temperature is 60-100°C.
[0012] According to the above scheme, the graded pore single crystal includes micropores and mesopores, wherein the size of the mesopores is adjustable within the range of 4.2-10.0 nm.
[0013] According to the above scheme, the graded hole single crystal HP-MIL-101 is a single crystal with a network-like octahedral structure having graded holes penetrating therethrough.
[0014] According to the above scheme, the metal salt is one of ferric chloride hexahydrate, aluminum chloride hexahydrate, magnesium chloride hexahydrate, cobalt chloride hexahydrate or nickel chloride hexahydrate.
[0015] According to the above scheme, the organic ligand is one of terephthalic acid, 2,5-dihydroxyterephthalic acid, 2-aminoterephthalic acid or 2-sulfonate monosodium terephthalate.
[0016] According to the above scheme, the molar ratio of the metal salt to the organic ligand is 1-8:1.
[0017] According to the above scheme, the precursor solution also includes a monovalent copper salt, that is, the metal salt, the organic ligand and the monovalent copper salt are uniformly mixed in a solvent to obtain a precursor solution, and the copper-bearing graded porous single crystal HP-Cu is finally obtained by reflux reaction. Ⅰ @MIL-101.
[0018] Preferably, the monovalent copper salt is cuprous chloride.
[0019] Preferably, the molar ratio of the monovalent copper salt to the organic ligand is 1-5:1, preferably 2-3:1, which can prevent the monovalent copper salt from agglomerating and ensure a higher loading amount.
[0020] According to the above scheme, after the reaction is completed, filtering, purification and drying are performed to obtain hierarchical porous single crystal HP-MIL-101. Preferably, the purification is washing with water for 2-4 times and purifying with methanol for 30-40 hours; the drying conditions are: vacuum drying at 50-70°C for 20-30 hours.
[0021] Provided is a method for preparing a copper-bearing graded-pore single crystal HP-Cu Ⅰ @Application of MIL-101 as adsorbent in ethane / ethylene gas separation.
[0022] According to the above scheme, the copper-loaded graded-pore single crystal HP-Cu Ⅰ @MIL-101 is kept at 40-80℃ for 8-12h before ethane / ethylene gas separation.
[0023] Beneficial effects of the present invention:
[0024] 1. The present invention provides a synthesis method of hierarchical pore single crystal HP-MIL-101 and its separation application, wherein a metal salt and an organic ligand are dissolved in water and then subjected to a reflux reaction, thereby obtaining hierarchical pore single crystal HP-MIL-101; wherein: the size of MOF mesopores can be adjusted by adjusting the volume of water; the obtained hierarchical pore single crystal MOF has a stable structure, a network-like octahedral structure with hierarchical pores running through it, and has both micropores and mesopores, a high specific surface area, and the mesopore size and single crystal purity are controllable; the preparation method is simple, the conditions are mild, and it has industrial application prospects.
[0025] 2. Further, by introducing monovalent copper into the raw material, copper-loaded graded porous single crystal HP-Cu can be obtained. Ⅰ @MIL-101-(OH) 2 It can be used as an adsorbent to separate ethylene and ethane. It preferentially adsorbs ethylene rather than ethane through π-complexation, thereby improving the selectivity of ethylene and ethane. The IAST selectivity of ethylene and ethane reaches 66 at 298K and 0.1bar, which is much higher than that of traditional adsorbent materials. It also has good stability and still has excellent adsorption capacity for ethylene after multiple cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD patterns of the metal organic framework materials prepared in Examples 1-4 and Comparative Example 1.
[0027] Figure 2 N is the metal organic framework material prepared in Examples 1-4 and Comparative Example 1 2 Adsorption-desorption curve (top) and pore size distribution (bottom).
[0028] Figure 3 This is a SEM image of the metal organic framework material prepared in Example 1; Figure 3 ad are HP-MIL-101(Fe)-(OH) 2 -1SEM images at different angles or scales.
[0029] Figure 4 TEM image of the metal organic framework material prepared in Example 1; Figure 4 ad are HP-MIL-101(Fe)-(OH) 2 -1TEM images at different angles or scales.
[0030] Figure 5 This is the adsorption curve of ethane / ethylene of the hierarchical porous single crystal metal organic framework material prepared in Example 1 and Example 4 at 298K; pressure: 0-1 bar.
[0031] Figure 6 The graded porous single crystal HP-Cu prepared in Example 4 Ⅰ @MIL-101(Fe)-(OH) 2 Cyclic adsorption of ethylene at 298 K. DETAILED DESCRIPTION
[0032] In order to make the purpose, method and advantages of the present invention more clear, the present invention is further described in conjunction with embodiments, but is not limited thereto.
[0033] Example 1
[0034] Provide a graded hole single crystal HP-MIL-101(Fe)-(OH) 2 The synthesis method comprises the following steps:
[0035] Weigh 2162.4 mg of ferric chloride hexahydrate, 396.3 mg of 2,5-dihydroxyterephthalic acid, and 60 mL of deionized water, mix evenly and ultrasonicate for 30 minutes, then put it into an 80°C oil bath for condensation and reflux reaction for 48 hours. After the reaction is completed, cool it to room temperature, filter it, wash it three times with water, purify it with methanol for 36 hours, and then put it into a 60°C vacuum drying oven for 24 hours to obtain an iron-based metal organic framework material, which is recorded as HP-MIL-101(Fe)-(OH) 2 -1.
[0036] like Figure 2 ,HP-MIL-101(Fe)-(OH) 2 -1 N 2 The adsorption-desorption curve is a type IV curve with an obvious hysteresis loop, indicating a mesoporous structure. The mesopore distribution curve shows that the mesopore size is 4.2 nm.
[0037] Figure 3 and Figure 4 HP-MIL-101(Fe)-(OH) 2 -1 presents a single crystal with a network of octahedral structures with hierarchical pores running through it, which makes the interior of the crystal have complex channels and pores, which is beneficial to the transmission and reaction of substances, helps to optimize the performance of the crystal, and can enhance the adsorption capacity.
[0038] Example 2
[0039] Provide a graded hole single crystal HP-MIL-101(Fe)-(OH) 2 The synthesis method comprises the following steps:
[0040] Weigh 2162.4 mg of ferric chloride hexahydrate, 396.3 mg of 2,5-dihydroxyterephthalic acid, and 120 mL of deionized water, mix evenly and ultrasonicate for 30 minutes, then put it into an 80°C oil bath for condensation and reflux reaction for 48 hours. After the reaction is completed, cool it to room temperature, filter it, wash it three times with water, purify it with methanol for 36 hours, and then put it into a 60°C vacuum drying oven for 12 hours to obtain an iron-based metal organic framework material, which is recorded as HP-MIL-101(Fe)-(OH) 2 -2.
[0041] like Figure 2 ,HP-MIL-101(Fe)-(OH) 2 -2 N 2The adsorption-desorption curve is a type IV curve with an obvious hysteresis loop, indicating that it has a mesoporous structure. The mesopore distribution curve shows that the mesopore size is 5.5 nm.
[0042] Example 3
[0043] Provide a graded hole single crystal HP-MIL-101(Fe)-(OH) 2 The synthesis method comprises the following steps:
[0044] Weigh 2162.4 mg of ferric chloride hexahydrate, 396.3 mg of 2,5-dihydroxyterephthalic acid, and 200 mL of deionized water, mix evenly and ultrasonicate for 30 minutes, then put it into an 80°C oil bath for condensation and reflux reaction for 48 hours. After the reaction is completed, cool it to room temperature, filter it, wash it three times with water, purify it with methanol for 36 hours, and then put it into a 60°C vacuum drying oven for 12 hours to obtain an iron-based metal organic framework material, which is recorded as HP-MIL-101(Fe)-(OH) 2 -3.
[0045] like Figure 2 ,HP-MIL-101(Fe)-(OH) 2 -3 N 2 The adsorption-desorption curve is a type IV curve with an obvious hysteresis loop, indicating that it has a mesoporous structure with a mesopore size of 10.0 nm.
[0046] Example 4
[0047] Provide a copper-loaded graded hole single crystal HP-Cu Ⅰ @MIL-101(Fe)-(OH) 2 The synthesis method comprises the following steps:
[0048] Weigh 2162.4 mg of ferric chloride hexahydrate, 396.3 mg of 2,5-dihydroxyterephthalic acid, 396 mg of cuprous chloride, and 60 mL of deionized water, mix evenly and ultrasonicate for 30 minutes, then place in an 80°C oil bath for condensation and reflux reaction for 48 hours. After the reaction is completed, cool to room temperature, filter, wash three times with water, purify with methanol for 36 hours, and place in a 60°C vacuum drying oven for 12 hours to obtain an iron-based metal organic framework material, recorded as HP-Cu Ⅰ @MIL-101(Fe)-(OH) 2 .
[0049] like Figure 2 , HP-Cu Ⅰ @MIL-101(Fe)-(OH) 2 N 2The adsorption-desorption curve is a type IV curve with an obvious hysteresis loop, indicating that it has a mesoporous structure. The mesopore size is 3.9 nm, and its hierarchical pore structure is still maintained.
[0050] The hierarchical porous single crystal HP-MIL-101 prepared in Example 1 and Example 4 was used as an adsorbent to carry out ethane / ethylene adsorption separation, and the specific steps were as follows:
[0051] 80 mg of the obtained hierarchical porous single crystal metal organic framework material was weighed and vacuum dried at 80° C. for about 10 h to obtain an activated adsorbent, and then its single component adsorption curve for ethane and ethylene was tested at 298K.
[0052] Figure 5 The adsorption curve of ethane / ethylene by the hierarchical porous single crystal metal organic framework material prepared in Example 1 and Example 4 at 298K. The figure shows that the copper-loaded hierarchical porous adsorbent HP-Cu Ⅰ @MIL-101(Fe)-(OH) 2 At 298K and 1 bar, the adsorption capacities of ethylene and ethane are 3.4 mmol / g and 1.1 mmol / g, respectively. The calculated IAST selectivity can reach 8. In addition, at 0.1 bar, the adsorption capacity of C 2 H 4 / C 2 H 6 The IAST selection performance reaches 66, which is higher than many benchmark materials.
[0053] The IAST selectivity of gas, i.e. the gas selectivity based on the Ideal Adsorbed Solution Theory (IAST), refers to the separation performance or selectivity of different gas components in the adsorption process in porous materials calculated using the IAST theory. This theory is often used to predict and evaluate the adsorption and separation capabilities of porous materials (such as metal organic frameworks, ultra-microporous carbon adsorbents, etc.) for mixed gas components.
[0054] Figure 6 The graded porous single crystal HP-Cu prepared in Example 4 Ⅰ @MIL-101(Fe)-(OH) 2 The cyclic adsorption capacity diagram of ethylene at 298K shows that the adsorption capacity of ethylene by the graded pore single crystal is still 3.3mmol / g in six consecutive adsorption cycles, and the high ethylene adsorption capacity is still maintained, indicating that the obtained graded pore single crystal has good recyclability.
[0055] Comparative Example 1
[0056] A method for synthesizing a metal organic framework material is provided, comprising the following steps:
[0057] Weigh 2162.4 mg of ferric chloride hexahydrate, 396.3 mg of 2,5-dihydroxyterephthalic acid, and 20 mL of deionized water, mix evenly and ultrasonicate for 30 minutes, then put it into an 80°C oil bath for condensation and reflux reaction for 48 hours. After the reaction is completed, cool it to room temperature, filter it, wash it three times with water, purify it with methanol for 36 hours, and then put it into a 60°C vacuum drying oven for 12 hours to obtain an iron-based metal organic framework material, recorded as MIL-101(Fe)-(OH) 2 .
[0058] like Figure 2 ,MIL-101(Fe)-(OH) 2 N 2 The adsorption-desorption curve is a typical microporous curve without hysteresis loop, indicating a microporous structure.
[0059] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
Claims
1. A method for synthesizing hierarchical porous single crystal HP-MIL-101, characterized in that: The steps include: The metal salt and the organic ligand are uniformly mixed in water to obtain a precursor solution, which is then heated for reflux reaction. After the reaction is completed, the graded hole single crystal HP-MIL-101 is obtained; wherein: The molar volume ratio of organic ligand to water is 1 mol:30-100 L; The reflux reaction time is: 40-96h.
2. The synthesis method according to claim 1, characterized in that The heating temperature is 60-100℃.
3. The synthesis method according to claim 1, characterized in that The graded pore single crystal includes micropores and mesopores, wherein the size of the mesopores is adjustable in the range of 4.2-10.0 nm.
4. The synthesis method according to claim 1, characterized in that The metal salt is one of ferric chloride hexahydrate, aluminum chloride hexahydrate, magnesium chloride hexahydrate, cobalt chloride hexahydrate or nickel chloride hexahydrate; the organic ligand is one of terephthalic acid, 2,5-dihydroxyterephthalic acid, 2-aminoterephthalic acid or monosodium 2-sulfonateterephthalate.
5. The synthesis method according to claim 1, characterized in that The molar ratio of the metal salt to the organic ligand is 1-8:
1.
6. The synthesis method according to claim 1, characterized in that The precursor solution also includes monovalent copper salt, and finally obtains copper-loaded graded porous single crystal HP-Cu Ⅰ @MIL-101.
7. The synthesis method according to claim 6, characterized in that The monovalent copper salt is cuprous chloride.
8. The synthesis method according to claim 6, characterized in that The molar ratio of the monovalent copper salt to the organic ligand is 1-5:
1.
9. The synthesis method according to claim 8, characterized in that The molar ratio of the monovalent copper salt to the organic ligand is 2-3:
1.
10. A copper-bearing hierarchical porous single crystal HP-Cu prepared by the preparation method according to any one of claims 6 to 9 Ⅰ @Application of MIL-101 as adsorbent in ethane / ethylene gas separation.
Citation Information
Patent Citations
Graded hole NiO / C electrochromic display device and preparation method and application thereof
CN108919585A
Application of Fe-based metal organic framework material as combustion catalyst
CN114768873A
Controllable preparation method of silver-loaded grading hole forming adsorbent and application of adsorbent in ethane / ethylene adsorption separation
CN117960136A
Semiconductor memory dedvice
KR1020220166604A
Method for maintaining security for sensitive information and apparatus using the method
KR102091388B1